Pre-gestational diabetes in a young woman with a pathogenic INSR missense mutation, p.(Met1180Lys) - Emma L Prehn; Mairéad Crowley; David Fennell; Brendan T Kinsley; Kevin Colclough; Maria M Byrne (Endocrinology, Diabetes & Metabolism Case Reports)
Heterozygous insulin receptor (INSR) mutations cause type A insulin resistance (IR), associated with a phenotype of IR; hyperandrogenism, oligomenorrhoea and acanthosis nigricans in the absence of obesity or lipoatrophy. The phenotype is variable, ranging from neonatal hyperinsulinaemic hypoglycaemia to fasting or post-prandial hypoglycaemia in adults to diabetes. We report a 29-year-old woman presenting at 13 weeks gestation in her second pregnancy. Diabetes was diagnosed at 13-years-old following presentation with lethargy and polyuria and she was treated with metformin 500 mg po bd. She also had polycystic ovarian syndrome, hypothyroidism and epilepsy. Metformin was changed to insulin with good glycaemic control throughout pregnancy. She delivered a 3.95 kg male infant at 39 weeks gestation without neonatal hypoglycaemia. At 18 months post-partum, her body mass index was 26.3 kg/m2, with no evidence of acanthosis nigricans or features of lipodystrophy. As her sister was also diagnosed with diabetes at 13-years-old, next-generation sequencing was performed for known maturity onset diabetes of the young (MODY) genes and a p.(Met1180Lys) mutation in the INSR gene was detected. She reported nocturnal hypoglycaemia and a 5-h oral glucose tolerance test revealed post-prandial hyperinsulinaemic hypoglycaemia at 210 min. Her subsequent pregnancy was spontaneously treated with metformin 500 mg po od from 8 to 25 weeks gestation and discontinued due to intrauterine growth restriction. She delivered a 1.8 kg female infant at 34 plus 3 weeks gestation (25th centile) via elective caesarean section. The infant had transient neonatal hypoglycaemia for two days. Post-partum, she remains diet controlled, with a haemoglobin A1c of 32 mmol/mol. This case highlights the importance of genetic testing to establish optimal diabetes treatment.